2007
DOI: 10.1021/bm070085x
|View full text |Cite
|
Sign up to set email alerts
|

PEG-SS-PPS:  Reduction-Sensitive Disulfide Block Copolymer Vesicles for Intracellular Drug Delivery

Abstract: Under appropriate conditions, block copolymeric macroamphiphiles will self-assemble in water to form vesicles, referred to as polymersomes. We report here polymersomes that can protect biomolecules in the extracellular environment, are taken up by endocytosis, and then suddenly burst within the early endosome, releasing their contents prior to exposure to the harsh conditions encountered after lysosomal fusion. Specifically, block copolymers of the hydrophile poly(ethylene glycol) (PEG) and the hydrophobe poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
364
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 418 publications
(373 citation statements)
references
References 44 publications
7
364
0
2
Order By: Relevance
“…On the one hand, low-T g polymers have the advantage of being readily formed at normal production temperatures, thus approaching equilibrium micelle size and shape; on the other hand, higher-T g hydrophobic block compositions (T g >37 °C) or crystalline hydrophobic polymers (T m >37 °C) self-assemble at supraphysiological temperatures for very stable use at 37 °C, below T g or T m . Micelle, and also polymersome 35 (see below), processability can thus be engineered by manipulating any of the mat erial parameters mentioned above to exploit the equilibrium nature of the materials, as well as by slowing the dissociation rate to suit practical use. Biologically derived molecules may also readily self-assemble, as can be observed in virus-like particles, which are now in clinical use.…”
Section: Materials For Penetrating Tissue Barriersmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, low-T g polymers have the advantage of being readily formed at normal production temperatures, thus approaching equilibrium micelle size and shape; on the other hand, higher-T g hydrophobic block compositions (T g >37 °C) or crystalline hydrophobic polymers (T m >37 °C) self-assemble at supraphysiological temperatures for very stable use at 37 °C, below T g or T m . Micelle, and also polymersome 35 (see below), processability can thus be engineered by manipulating any of the mat erial parameters mentioned above to exploit the equilibrium nature of the materials, as well as by slowing the dissociation rate to suit practical use. Biologically derived molecules may also readily self-assemble, as can be observed in virus-like particles, which are now in clinical use.…”
Section: Materials For Penetrating Tissue Barriersmentioning
confidence: 99%
“…Earlier in the processes of endolysosomal processing, endocytosed nanoparticles encounter a reductive environment. Self-assembling block co-polymers with architecture PEG-SS-PPS, that is with a reducible disulphide connection between the hydrophobic and hydrophilic blocks, have been shown to destabilize within 15 min of endocytosis in a macrophagelike cell line (a model of APCs), releasing the contents of the polymersomes within the early endosome 35 . Linear multiblock co-polymers have also been developed; they consist of DNA-binding peptides that are flanked on each side by a cysteine residue and polymerized by oxidation in vitro 50 .…”
Section: Materials For Intracellular Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] In another example, Cerritelli et al observed faster cytoplasm release of calcein from NPs formed using PEG-SS-poly(propylene sulfide) copolymers when compared with a non-cleavable formulation. [8] However, so far, assays to evaluate PEG shedding are end-point focused and yield no information of PEG shedding process during NP-cell interactions. In addition, these functional assays are unique to the delivery of the specific payloads, and thus may not be generalized across NP systems.…”
mentioning
confidence: 99%
“…Both conjugation and deprotection reactions are confirmed by the ninhydrin test. The resin is then reacted with amine-reactive OG488 dyes to assemble (8). Since the thiol of cystine is protected by a trityl group, thiol deprotection and resin cleavage can thus be carried out in a single TFA treatment.…”
mentioning
confidence: 99%